Factors associated with sleep quality among Malaysian undergraduate students during the COVID-19 pandemic - Ee, Yx; Gan, Wan Ying (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Poor sleep quality has become a public health concern due to its association with several health risks. Recent studies had shown that university students had poor sleep quality during the COVID-19 pandemic. Thus, this study aimed to determine the factors associated with sleep quality among undergraduate students in Malaysia during the COVID-19 pandemic. This cross-sectional study involved 377 undergraduates from public and private universities in Malaysia. The study ws conducted between 16 June 2021 to 31 July 2021. Respondents completed an online survey reagarding to their sociodemographic background, sleep quality, chronotype pattern, night eating syndrome, food security, physical activity, internet addiction and self-reported body weight and height. There was poor sleep quality in 62.3% of the respondents. Respondents who were Malay (AOR = 3.84, 95% CI =2.07-7.11), in the arts stream (AOR = 2.55, 95% CI = 1.20-5.42) and internetaddicted (AOR = 2.14, 95% CI = 1.22-3.77) had higher risk of poor sleep quality. Respondents who lived in a rented house (AOR = 0.38, 95% CI = 0.16-0.88), were sophomores (AOR = 0.49, 95% CI = 0.25-0.99) and were the morning chronotype (AOR = 0.35, 95% CI = 0.17-0.72) had lower risk for developing poor sleep quality. This study underscored the high prevalence of poor sleep quality among undergraduate students during the COVID-19 pandemic. The findings suggested that by preventing internet addiction and the evening chronotype can improve sleep quality.